2023
DOI: 10.1063/5.0138920
|View full text |Cite
|
Sign up to set email alerts
|

Memristor bridge synapse for better artificial neuron perceptron

Abstract: In artificial neural networks, the fourth passive element memristor can be utilized as an electronic synapse that serves as the interface between neurons. The artificial neuron composed of the memristor bridge synapse not only has the characteristics of low power consumption and high integration but also has a more simplified circuit and weight change conditions. Particularly, it has the ability of bionic intelligent information processing. This paper established two novel synaptic structures on the basis of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…The ndings of this thesis might be suitable for realizing the core of a spiking neural network architecture using two different types of memristor-based synapse circuitry improved by concentrating on state-of-the-art [10] and con guring a memristor to function as a synapse, enabling the STDP learning process aiming to achieve a low-power neuromorphic computing structure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ndings of this thesis might be suitable for realizing the core of a spiking neural network architecture using two different types of memristor-based synapse circuitry improved by concentrating on state-of-the-art [10] and con guring a memristor to function as a synapse, enabling the STDP learning process aiming to achieve a low-power neuromorphic computing structure.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, we have recon gured the synaptic circuits as our new ndings for a better arti cial neuron perceptron, the 2 memristor bridge synapse circuit (type 1, type 2) proposed by N. Wang et al, where they showed better symmetry of the synaptic weight with a wider range of weight updates [10]. We named two synaptic circuits two-resistor one capacitor (2R1C) and two-transistor one capacitor (2T1C)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation